2017
DOI: 10.18203/2320-1770.ijrcog20170558
|View full text |Cite
|
Sign up to set email alerts
|

Lateral location of placenta on ultrasound as a predictive test for preeclampsia

Abstract: Background: Hypertensive disorders represent the most common medical complication of pregnancy Pre-eclampsia complicates approximately 2-7% of pregnancies and is a major cause of maternal and perinatal morbidity This has led to the interest in screening. The placenta is located laterally in majority of patients with abnormal flow velocity waveforms. In the light of these observations, we designed a prospective study to find out whether the lateral location of placenta as seen by ultrasound at II and III trimes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
2
1
0
Order By: Relevance
“…The prevalence of pre-eclampsia in this study was 14% which is similar to previous studies with 14%, 9 and another study with 13.6% prevalence of pre-eclampsia. 10 This study result concurs with Kofinas et al, who observed that women with a unilateral placenta had a 2.8-fold higher risk of preeclampsia than those with a centrally located placenta.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of pre-eclampsia in this study was 14% which is similar to previous studies with 14%, 9 and another study with 13.6% prevalence of pre-eclampsia. 10 This study result concurs with Kofinas et al, who observed that women with a unilateral placenta had a 2.8-fold higher risk of preeclampsia than those with a centrally located placenta.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of pre-eclampsia in this study was 14% which is similar to previous with 14%, 9 and another study with 13.6% prevalence of pre-eclampsia. 10 This study result concurs with Kofinas et al, who observed that women with a unilateral placenta had a 2.8-fold higher risk of preeclampsia than those with a centrally located placenta.…”
Section: Discussionsupporting
confidence: 91%
“…Among 47 women with preeclampsia, 23 (48.94%) and in normotensive women, 44 (53.01%) were in the age group 21-25 years. In our study, in the 21-25 age group 48.9% of women with preeclampsia were present, which was found to be higher than in other studies such as Kaku et al [ 12 ], Nandanwar et al [ 13 ], Aggarawal et al [ 14 ] as 46%, 46%, 43% were found to have preeclampsia in the 21-25 age group. Still, the Nanthini et al study [ 15 ] was higher than our study, as 53% of women were found to have preeclampsia in the same age group.…”
Section: Discussioncontrasting
confidence: 63%
“…The study by Nanthini et al [ 15 ] and Naik et al [ 10 ] was comparable to our study. In the Kaku et al [ 12 ] study, preeclampsia appeared 30-34 weeks earlier than ours. In women with preeclampsia, among 47 women, 32 (68.09%) were diagnosed with preeclampsia between 36-39 weeks of pregnancy.…”
Section: Discussioncontrasting
confidence: 48%